Skin cancer in the white and black population in Brazil: Prevalence, morbidity, and mortality (Research, Society and Development, 2025)
Skin cancer is a major public health problem in Brazil, with incidence rates constantly rising, according to data from the National Cancer Institute. Scientific literature shows that skin phototype, i.e. skin color, is a significant risk factor, with fair-skinned individuals being more susceptible to developing the disease. However, skin cancer mortality is proportionally higher in black individuals, possibly due to late diagnosis, aggravated by socioeconomic, cultural and historical factors. In addition, exposure to ultraviolet rays (UVA and UVB) is the main environmental factor associated with the development of skin cancer. Analysis of available studies reveals that primary prevention, through measures such as adequate use of sunscreen and adopting strategies to minimize direct exposure to the sun, is essential to reduce the incidence of the disease. Given this, the objective of this study was to compare the different prognoses of skin cancer in white and black populations, in addition to describing the main factors that lead to the increase in the rates of this disease in Brazil. Finally, we highlight that promoting early diagnosis, through educational campaigns and access to periodic dermatological examinations, especially for vulnerable populations, is essential to improve prognosis and reduce mortality from skin cancer.